HIGH QUALIFIED FREE WRESTLERS PRE-COMPETITION IN THE PHASE FUNCTIONAL MONITORING THE SITUATION - Arslanov Qahramon Polvonovich (International Journal of Literature and Language Studies, 2026)
This article examines the issues of systematic monitoring of the functional state of highly qualified freestyle wrestlers during the pre-competitive preparation stage. In the course of the study, the adaptation characteristics of the athletes' cardiovascular, respiratory, and neuromuscular systems to training loads were analyzed using modern diagnostic methods. It is substantiated that continuous control of functional parameters at the pre-competitive stage helps prevent overtraining states and ensures reaching the peak of athletic form. The results obtained serve as a basis for developing practical recommendations for the individual correction of training volume and intensity.